Dampak Kebijakan Luar Negeri Amerika Serikat terhadap African Growth and Opportunity Act (Agoa) Bagi Pembangunan di Afrika Selatan - Mahsa Kaulika; Arie Kusuma Paksi (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
As a superpower country that plays an essential role in supporting the development of third-world countries, the United States of America issued a policy made explicitly for countries in the Sub-Saharan African  countries. This study attempts to discuss African Growth and Opportunity Act (AGOA) as a foreign policy initiated by the United States as the leading actor in providing economic assistance to support the development in Africa. This study uses the concept of foreign policy to achieve the state’s national interest. It uses the qualitative method to collect the data needed to fulfill the information regarding the author’s topic. This study finds that this policy immensely helped Africa become a productive region and compete internationally. Although its application has many challenges, AGOA generally grants both parties. The increasing development of the global world that has become more complex and the change of the leader of the U.S. has made this U.S. foreign policy within the AGOA run dynamically, which means that it can shift according to the circumstances.